2019
DOI: 10.1038/s41598-019-46555-4
|View full text |Cite
|
Sign up to set email alerts
|

HDAC6 depletion improves cystic fibrosis mouse airway responses to bacterial challenge

Abstract: The hypothesis of this study was that Hdac6 depletion would restore cystic fibrosis (CF) responses to bacterial challenge to more wild type profiles using a CF mouse model. CF mice harboring the F508del Cftr mutation respond to bacterial challenge with 25,000 CFU Pseudomonas aeruginosa embedded into agarose beads to slow clearance. CF mice respond significantly more aggressively to this challenge compared to WT mice with respect to bacterial clearance, weight loss, neutrophil recruitment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(46 citation statements)
references
References 57 publications
5
41
0
Order By: Relevance
“…Examining the importance of HDAC6 in vivo in a CF context, we demonstrated that depletion of Hdac6 expression from a CF mouse model increased CF mouse linear growth, increased weight gain, and restored the ability to store fat 22 . We also demonstrated the depletion of Hdac6 in CF mice normalizes the inflammatory response and the ability to clear bacteria in a murine airway infection model 23 . The restoration of linear growth and the increase in insulin-like growth factor-1 (IGF-1) in CF mice lacking Hdac6 expression suggests that the hypothalamus-pituitary axis is being affected by Hdac6 depletion indicating a direct neurological impact 24,25 .…”
mentioning
confidence: 65%
See 3 more Smart Citations
“…Examining the importance of HDAC6 in vivo in a CF context, we demonstrated that depletion of Hdac6 expression from a CF mouse model increased CF mouse linear growth, increased weight gain, and restored the ability to store fat 22 . We also demonstrated the depletion of Hdac6 in CF mice normalizes the inflammatory response and the ability to clear bacteria in a murine airway infection model 23 . The restoration of linear growth and the increase in insulin-like growth factor-1 (IGF-1) in CF mice lacking Hdac6 expression suggests that the hypothalamus-pituitary axis is being affected by Hdac6 depletion indicating a direct neurological impact 24,25 .…”
mentioning
confidence: 65%
“…Inflammation has been correlated with depression in a number of studies 35 38 , therefore, alleviating inflammatory signaling may be a mode of action of Hdac6 depletion. We have shown specifically in CF mouse models that depletion of Hdac6 results in reduced inflammation and better clearance of bacteria in airways from infected mice 23 . Several studies have demonstrated the anti-inflammatory benefits of HDAC6 inhibition, with two specifically looking at neuronal inflammation.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The treatment of CF patients, carrying at least one copy of the G551D mutation, with Ivacaftor leads to reduced migration and activation of neutrophils [129], as well as improved bacterial clearance in this cohort of patients [127]. Another potential therapeutic target for CF was proposed to be histone deacetylase 6 (HDAC6), as its depletion, in a mouse model, reduced the recruitment of neutrophils to the lungs, followed by an improved response to infection and an increased rate of bacterial clearance and reduced weight loss [130].…”
Section: Neutrophilsmentioning
confidence: 99%